System wspomagania prognozowania z ograniczeniami kalendarzowymi - Gołuchowski, Jerzy; Kania, Krzysztof (Forecasting support system with calendar constraints, 2005)
The paper addresses issues related to the problem of forecasting with a calendar constraints. In many cases calendar constraints can be omitted, in other ones a calendar has a decisive influence on the analysed phenomena. Especially in the business environment this problem is often seen. In the paper, by a particular example of business activity we present a new simply approach to resolve this problem.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 58-66